Studi Meaning of Life Siswa Sekolah Menengah Pertama Etnis Tengger - Ningsih, Y Mentari Catur Riyadi; Hidayah, Nur; Lasan, Blasius Boli (Jurnal Kajian Bimbingan dan Konseling, 2017)
This is an experimental study which describes the effectiveness of group counseling treatment in increasing student’s confidence. The subject of this study is IX grade students of Sekolah Menengah Pertama Negeri 1 Paciran, Lamongan, East Java. The subject which can be said as sample of the study were collected using purposive sampling. They were divided into two groups namely experiment group and control group. Both group was given different treatment and the result of those treatments were examined using Wilcoxon Signed Ranks Test. The result shows that group counseling treatment can improve student’s confidence.